DEMOCRACY AND THE WESTERN LIBERAL INTERPRETATION OF HUMAN RIGHTS IN THE CONTEXT OF COVID-19 PANDEMIC - Tirimanna, Vimal (Asian Horizons, 2020)
Covid-19 virus has re-evoked an important social ethical point, namely, the fact that we humans are social beings and not isolated monads. In the new ‘normal’ set up all over the world, one has to learn to live with the virus but this demands a sense of responsibility from each and every human person in a given society. It is this sense of social responsibility rather than a mere insistence on the rights of a human being (that ignores the corresponding duties) that has been stressed by the Catholic social doctrine in total contrast to the exclusive individualistic interpretation of human rights in the Western liberal tradition into which human rights were born first. This article aims at pointing out that the social doctrine of the Church has something important to contribute in filling the glaring lacuna of the one-sided Western liberal interpretation of rights. For any democracy to function effectively, such a balanced view of rights accompanied by the promotion of common good is indispensable.